2022
DOI: 10.3389/fimmu.2022.834650
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Dysregulated Long Non-Coding RNAs in HBV-Related Hepatocellular Carcinoma

Abstract: Infection with the hepatitis B virus (HBV) continues to pose a major threat to public health as approximately 292 million people worldwide are currently living with the chronic form of the disease, for which treatment is non-curative. Chronic HBV infections often progress to hepatocellular carcinoma (HCC) which is one of the world’s leading causes of cancer-related deaths. Although the process of hepatocarcinogenesis is multifaceted and has yet to be fully elucidated, several studies have implicated numerous l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 112 publications
(147 reference statements)
0
3
0
Order By: Relevance
“…PRC1 is overexpressed in human hepatocellular carcinoma cells and it is associated with the increased chemoresistance of these cells [ 55 ]. PRC1-AS1 is an antisense lncRNA and, similarly to PRC1, is associated with hepatocellular carcinoma [ 35 ]. The intronic region where the SNP is located is conserved only in primates with the exception of marmoset and squirrel monkey, while in rat, mouse and pig it is not conserved.…”
Section: Resultsmentioning
confidence: 99%
“…PRC1 is overexpressed in human hepatocellular carcinoma cells and it is associated with the increased chemoresistance of these cells [ 55 ]. PRC1-AS1 is an antisense lncRNA and, similarly to PRC1, is associated with hepatocellular carcinoma [ 35 ]. The intronic region where the SNP is located is conserved only in primates with the exception of marmoset and squirrel monkey, while in rat, mouse and pig it is not conserved.…”
Section: Resultsmentioning
confidence: 99%
“…They also cause HCC therapy resistance [78] . Several studies have shown that particular lncRNAs can be directly or indirectly disregulated by the HBx protein [79][80][81] [Table 1].…”
Section: Epigenetic and Genetic Alterationsmentioning
confidence: 99%
“…Moreover, the primary roles of these lncRNAs are to inhibit tumor suppressors and/or increase oncogene expression and HBV replication. It has been discovered that barely any lncRNAs inhibit the growth of tumors, and these are frequently inhibited in HCC [ 57 ].…”
Section: Introductionmentioning
confidence: 99%